Preparation of polypropylene with high melt strength by wet reaction blending of lignin. Issue 1 (18th June 2021) - Tian, Bo; Li, Jinfeng; Li, Zhigang; Dong, Wei; Zhang, Nan; Zhao, Hongtao; Liu, Yuguang; Di, Mingwei
Abstract: In this paper, the melt strength of polypropylene is shown to be significantly improved by lignin‐cooperative construction of heterophase network structure and the evolution mechanism of lignin on the topology of polypropylene is investigated. Electron paramagnetic resonance (EPR) analysis shows that the free radicals generated by polypropylene irradiation can remain active for 2 weeks; rheological studies show that lignin promotes the formation of heterogeneous network structures in polypropylene, and its melt is characterized by long‐chain branching. Phase angle‐complex modulus, complex viscosity‐complex modulus, Han's, and Cole–Cole curves are used to analyze the liquid–solid transformation, and the results indicate that the enhanced interfacial action is due to the formation of the heterogeneous network structures. The mechanical properties show that the impact strength is increased by 1.8 times due to the synergistic effect of lignin and acrylamide. SEM shows the formation of a fibrous network structure around the lignin, which undergoes interfacial yielding, improving the interfacial interaction between the components. Abstract :